BLUFÆRDIGHEDENS MAGT, MAGTENS BLUFÆRDIGHED: Prins Henriks nøgenbilleder - Arcand, Bernard (Tidsskriftet Antropologi, 1997)
Bernard Arcand: The Power of Modesty and the Modesty of Power. The Nude Pictures of Prince Henrik This article argues that pomography requires modesty almost as much as nudity, in order to piease its audience by adding to the spectacle of sex some feeling of conquest. Modesty appears as a primary notion at the root of social life: from the book of Genesis, when Adam and Eve express shyness, to the teachings of the Touareg on the proper use of the veil and to the recent surge of so-called “amateur pomography”. Modesty translates how others become fascinating and attractive, an obvious pre-requisite for Creative interaction.